How selfish individuals achieve unselfish goals: majority-based progressive control of discrete event systems. Issue 9 (1st September 2020) - Park, Seong-Jin; Yang, Jung-Min
ABSTRACT: We present majority-based progressive control in which local supervisors have not only their own private specifications as primary goals, but an additional global specification representing a desirable behavior of the overall system. The control policy follows the majority rule, and the ultimate goal is to achieve a progressive closed-loop behavior whereby the number of local supervisors meeting private specifications increases as the controlled system evolves. For this purpose, we present the notion of majority-controllability of a global specification, and show that it is a crucial condition for the existence of local supervisors achieving a progressive global specification. Using the presented control theory, we analyze how the federal estate tax in the Unites States was repealed in 2010.